Christianity on display: a semiotic study of two museums of world religions (Glasgow, Taipei) - Min-Hsiu Liao (Church, Communication and Culture, 2021)
This article regards museums of world religions as intersemiotic sites where the knowledge of individual religions as well as religion as a broad concept is socially constructed. It examines the role of verbal interpretations in co-constructing knowledge of religion with other visual and spatial semiotics. The case study is based on a comparison of the text panels and the display cases on Christianity in two museums: St Mungo Museum of Religious Life and Art (SMM) in Glasgow, and Museum of World Religions (MWR) in Taipei. The methodology combines the micro-level analysis of theme-rheme pattern in information progression, logical-semantic relations in verbal-visual interaction, and a pragmatic account of the two epistemic communities in which the museums are situated. The results suggest that through the interaction between the text panels, labels, and individual objects, each museum has construed its own material definition of religion. Specifically, Christianity is construed as a phenomenon perceived by Christians in SMM, whereas in MWR, the knowledge of Christianity develops from the holy scriptures.